2019
DOI: 10.3171/2019.5.focus19279
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ventriculostomy-associated CSF infection with antibiotic-impregnated catheters in pediatric patients: a single-institution study

Abstract: OBJECTIVEExternal ventricular drains (EVDs) are commonly used in the neurosurgical population. However, very few pediatric neurosurgery studies are available regarding EVD-associated infection rates with antibiotic-impregnated EVD catheters. The authors previously published a large pediatric cohort study analyzing nonantibiotic-impregnated EVD catheters and risk factors associated with infections. In this study, they aimed to analyze the EVD-associated infection rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The median duration of HAV after the procedure in patients with EVD was 7 days (IQR 3-9), similar to the findings in the large cohort reported by Topjian et al, with a median time to positive culture of 7 days (IQR 4.75, 9), but a lower rate of HAV of 6% [21]. The same authors later demonstrated a significant decline in the ventriculostomy-associated CSF infection rate after the implementation of antibiotic-impregnated EVD catheters at their institution (0.9% vs. 6%, p = 0.00128) [22]. One study with a small number of preterm, low-birth-weight infants with post-hemorrhagic hydrocephalus found an infection rate of 7.7% (1/13) per patient and 4% (1/25) per procedure, using an antibiotic-impregnated EVD for a longer catheterization period [23].…”
Section: Discussionsupporting
confidence: 87%
“…The median duration of HAV after the procedure in patients with EVD was 7 days (IQR 3-9), similar to the findings in the large cohort reported by Topjian et al, with a median time to positive culture of 7 days (IQR 4.75, 9), but a lower rate of HAV of 6% [21]. The same authors later demonstrated a significant decline in the ventriculostomy-associated CSF infection rate after the implementation of antibiotic-impregnated EVD catheters at their institution (0.9% vs. 6%, p = 0.00128) [22]. One study with a small number of preterm, low-birth-weight infants with post-hemorrhagic hydrocephalus found an infection rate of 7.7% (1/13) per patient and 4% (1/25) per procedure, using an antibiotic-impregnated EVD for a longer catheterization period [23].…”
Section: Discussionsupporting
confidence: 87%
“…Most published studies on pediatric EVD placement concerned EVD-related infections, reported to occur in up to 37% [ 32 ] and varying usually from 0.9 to 20% [ 16 18 , 27 , 32 37 ]. A major problem is the choice of criteria for definition of an EVD-related infection [ 12 , 18 , 27 , 31 , 32 , 34 , 37 41 ]. Most centers based on their experience suggest to use specific institutional guidelines for EVD management to reduce infection rates [ 16 18 , 27 , 32 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the possibility of a selection of more aggressive bacteria by using such catheters is still discussed [ 43 ]. Lang et al recently reported a further reduction in infection rates from 6 to 0.9% when using antimicrobial-impregnated catheters, placed in the OR combined with postoperative care on the ICU [ 34 ]. Nevertheless, it remained unclear whether or not the location for EVD placement is relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic and foreign scholars have carried out a large number of studies on catheter-associated infection. Among them, Lang et al 27 used an antimicrobial-impregnated shunt catheter to make the drainage have antibacterial properties, which reduced the infection rate of CSF from 9% to 0.6%. 27 But the use of antibiotics brings with it the problem of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Lang et al 27 used an antimicrobial-impregnated shunt catheter to make the drainage have antibacterial properties, which reduced the infection rate of CSF from 9% to 0.6%. 27 But the use of antibiotics brings with it the problem of drug resistance. In addition, Lajcak et al 28 used silver-impregnated catheters to reduce the EVD infection rate significantly, 28 but the toxicity of silver is a problem that cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%